Timeout threshold estimation algorithm in mimic multiple executors architecture - Delei NIE; Obo ZHA; Chong WANG; Xin WANG; Binghao YAN (网络与信息安全学报)
Aiming at the problem that the current timeout strategy algorithm is difficult to cope with the violent situation of task volume,a timeout threshold prediction algorithm based on equivalent proportional execution time applied to the mimetic defense architecture system is proposed.The algorithm utilizes the principle that the execution time of multiple functional equivalent executable tasks in the mimetic defense architecture is positively related,predicts the task execution time and sets a reasonable timeout threshold.The simulation results show that the proposed algorithm can dynamically predict and set the timeout threshold for different task situations,which effectively improves the timeout judgment efficiency,especially for scenarios with dramatic changes in workload.